Clear Cell Adenocarcinoma Arising from Adenofibroma in a Patient with Endometriosis of the Ovary - Inju Cho; Sung-Chul Lim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Ovarian clear cell adenocarcinomas (CCACs) are frequently associated with endometriosis and, less often with clear cell adenofibromas (CCAFs). We encountered a case of ovarian CCAC arising from benign and borderline adenofibromas of the clear cell and endometrioid types with endometriosis in a 53-year-old woman. Regions of the adenofibromas showed transformation to CCAC and regions of the endometriosis showed atypical endometriotic cysts. This case demonstrates that CCAC can arise from CCAF or endometriosis.